Alija Izetbegovic-Thoughts of a Modern Muslim Thinker - Mulalic, Muhidin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Alija Izetbegovic-Thoughts of a Modern Muslim Thinker